Comparison of Small Gut and Whole Gut Microbiota of First-Degree Relatives With Adult Celiac Disease Patients and Controls - Bodkhe, Rahul; Shetty, Sudarshan A.; Dhotre, Dhiraj P.; Verma, Anil K.; Bhatia, Khushbo; Mishra, Asha; Kaur, Gurvinder; Pande, Pranav; Bangarusamy, Dhinoth K.; Santosh, Beena P.; Perumal, Rajadurai C.; Ahuja, Vineet; et al. (Frontiers in Microbiology, 2019)
Recent studies on celiac disease (CeD) have reported alterations in the gut microbiome. Whether this alteration in the microbial community is the cause or effect of the disease is not well understood, especially in adult onset of disease. The first-degree relatives (FDRs) of CeD patients may provide an opportunity to study gut microbiome in pre-disease state as FDRs are genetically susceptible to CeD. By using 16S rRNA gene sequencing, we observed that ecosystem level diversity measures were not significantly different between the disease condition (CeD), pre-disease (FDR) and control subjects. However, differences were observed at the level of amplicon sequence variant (ASV), suggesting alterations in specific ASVs between pre-disease and diseased condition. Duodenal biopsies showed higher differences in ASVs compared to fecal samples indicating larger disruption of the microbiota at the disease site. The duodenal microbiota of FDR was characterized by significant abundance of ASVs belonging to Parvimonas, Granulicatella, Gemella, Bifidobacterium, Anaerostipes and Actinomyces genera. The duodenal microbiota of CeD was characterized by higher abundance of ASVs from genera Megasphaera and Helicobacter compared to the FDR microbiota. The CeD and FDR fecal microbiota had reduced abundance of ASVs classified as Akkermansia and Dorea when compared to control group microbiota. In addition, predicted functional metagenome showed reduced ability of gluten degradation by CeD fecal microbiota in comparison to FDRs and controls. The findings of the present study demonstrate differences in ASVs and predicts reduced ability of CeD fecal microbiota to degrade gluten compared to the FDR fecal microbiota. Further research is required to investigate the strain level and active functional profiles of FDR and CeD microbiota to better understand the role of gut microbiome in pathophysiology of CeD.